Further characterization of the curative antibodies in Trypanosoma musculi infection. - Wechsler, D S (1988)
The ability of immune plasma (IP) taken from different donor strains of mice to cure Trypanosoma musculi infection in various recipient mouse strains, when given during the plateau phase of infection, was examined. C57BL/6, B10.A/SgSn, B10.D2/oSn, B10.D2/nSn, DBA/2, and BALB/c strains could be cured of parasitemia (giving 0.4 to 0.8 ml of IP per mouse), whereas A/J and C3H/HeN strains could not (giving up to 1.2 ml of IP per mouse). Noncure appeared to be associated with the high-plateau parasitemias (approximately 10(8] that developed in the latter strains since IP administered early in infection, when the parasite burden was similar to the plateau parasitemias (approximately 10(6] of strains that could be cured, was at least partially effective in A/J and C3H/HeN mice. The IP of any strain tested (C57BL/6, B10.D2/oSn, B10.D2/nSn, DBA/2, A/J, or C3H/HeN) could bring about elimination of trypanosomes in strains able to be cured. The potency of IP from different strains varied, being greater in the strains that developed higher-plateau parasitemias. Potency of IP appears to correlate positively with the titers of trypanosome-specific antibody of the immunoglobulin G2a isotype (the curative antibody). The role of the late-acting complement components was examined. In C5-deficient mice the course of infection was normal, although the elimination phase was delayed by a few days. Cure of parasitemia by IP administered during the plateau phase was equally effective in the presence or absence of C5 in either the donor or the recipient. When tested in vitro, however, IP only exhibited antitrypanosomal activity when added to infected blood taken from C5-sufficient strains of mice. We conclude that in vitro, under the conditions used in the assay, antibody-mediated destruction of the trypanosomes is brought about by complement-mediated lysis. This process, although it probably occurs to some extent, is unlikely to be the major mechanism of trypanosome elimination in vivo.